Supply chain planning of global electronics manufacturer for short life cycle products - Saxena, Suruchi (2014)
Today's industrial environment is becoming more and more volatile and product life cycles are getting shorter. In this scenario, it becomes very important for companies to reexamine their supply chain and to do effective operational planning. The following thesis proposes scientific methodologies to look at some issues of the supply chain such as Capacity Planning, Production and Procurement Planning. The performance of supply chain is limited by capacity constraints on the system. Hence, it becomes vital to plan capacity wisely in anticipation of certain demand. The thesis presents an effective method for planning capacity in terms of equipment selection and resource allocation. The next stage after Capacity Planning is that of production itself and various tactical modes for production management are suggested. One model utilizes a fast transportation mode to reduce lead-time while the other model tries to compensate for the obsolescence cost by introducing the concept of obsolescence risk. The high fluctuation in demand also gives rise to the need of an effective procurement plan so as to minimize excess and obsolescence costs. The amount of safety stock that needs to be set in such a sienario is presented, as inventory costs are a significant contribution to the excess costs incurred. The focus is on making the entire system more flexible at the minimum cost.